Genome-wide analysis of copper, iron and zinc transporters in the arbuscular mycorrhizal fungus Rhizophagus irregularis - Tamayo, Elisabeth; Gómez-Gallego, Tamara; Azcón-Aguilar, Concepción; Ferrol, Nuria (Frontiers in Plant Science, 2014)
Arbuscular mycorrhizal fungi (AMF), belonging to the Glomeromycota, are soil microorganisms that establish mutualistic symbioses with the majority of higher plants. The efficient uptake of low mobility mineral nutrients by the fungal symbiont and their further transfer to the plant is a major feature of this symbiosis. Besides improving plant mineral nutrition, AMF can alleviate heavy metal toxicity to their host plants and are able to tolerate high metal concentrations in the soil. Nevertheless, we are far from understanding the key molecular determinants of metal homeostasis in these organisms. To get some insights into these mechanisms, a genome-wide analysis of Cu, Fe and Zn transporters was undertaken, making use of the recently published whole genome of the AMF Rhizophagus irregularis. This in silico analysis allowed identification of 30 open reading frames in the R. irregularis genome, which potentially encode metal transporters. Phylogenetic comparisons with the genomes of a set of reference fungi showed an expansion of some metal transporter families. Analysis of the published transcriptomic profiles of R. irregularis revealed that a set of genes were up-regulated in mycorrhizal roots compared to germinated spores and extraradical mycelium, which suggests that metals are important for plant colonization.